The Effect Of Giving Family’s Psychososial Stimulation On Social Development Of Children With Autism Spectrum Disorder (ASD) At ADIP Center Therapy Sumber Bendo Kediri Regency - Luluk Susiloningtyas; Nurin Fauziyah; Ratih Kusuma Wardhani (Universitas STRADA Indonesia, 2020)
Psychosocial stimulation served as a beneficial reinforcer for child development. Good psychosocial stimulation has a positive impact on the social development particularly for children with ASD. These study used a Quasi Experiment with Non-equivalent Control Group Design. The research analysis of the Mann Whitney test showed a significance of Sig (p) = 0.034. α = 5% = 0.05, p <α means there are differences in social development of children with Autism Spectrum Disorder (ASD) in the treatment group with the control group, it means that there is a difference after the treatment of giving psychosocial stimulation by the family. The analysis was performed using the Wilcoxon test, it was found that Sig (p) = 0.003. α = 5% = 0.05, p <α, it means that there is an effect of giving psychosocial stimulation by the family on the social development of children with Autism Spectrum Disorder (ASD).